2021
DOI: 10.17582/journal.jahp/2021/9.4.512.523
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Vitamin E and Panax ginseng Against Some Adverse Effects of Levofloxacin in Male Rats

Abstract: L evofloxacin is a third-generation, strictly synthetic flouroquinolone antibiotic. It has bactericidal activity against a wide variety of bacteria that are gram positive (G+ve) and gram negative (G-ve) (Al-Soufi and Al-Rek-abi, 2019). The principal target of quinolones is DNA gyrase, an essential bacterial enzyme (Abdel-Alim et al., 2017). Several studies have recorded that the most common serious effects associated with fluoroquinolones are headache, diarrhea, oxidative stress, hemolytic anemia, liver and ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…(P>0.05) of rats in Group VI showed non-significant difference compared to the Group III and group V showed non -significant elevation compared to group VI. These results consistent with that observed in previous studies (26) (27) Although levofloxacin has been proven to have certain negative effects on blood parameters in rats ، there is no obvious mechanism by which it reduces levels of packed cell volume (PCV) ، hemoglobin (HB) ، and mean corpuscular hemoglobin concentration (MCHC). Some studies show that the decrease in PCV ، HB ، and MCHC may be attributable to levofloxacin's ability to inhibit bone marrow (28) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…(P>0.05) of rats in Group VI showed non-significant difference compared to the Group III and group V showed non -significant elevation compared to group VI. These results consistent with that observed in previous studies (26) (27) Although levofloxacin has been proven to have certain negative effects on blood parameters in rats ، there is no obvious mechanism by which it reduces levels of packed cell volume (PCV) ، hemoglobin (HB) ، and mean corpuscular hemoglobin concentration (MCHC). Some studies show that the decrease in PCV ، HB ، and MCHC may be attributable to levofloxacin's ability to inhibit bone marrow (28) .…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore ، the animals declare non -significant elevated difference (P>0.05) of rats (neutrophil ، lymphocyte ، monocyte and eosinophil) level in Group II comparing negative control Group I rats ، in addition no significant (P>0.05) was observed in (neutrophil ، lymphocyte ، monocyte ، eosinophil) level in Group III compared to negative control Group I rats ، moreover Group IV resulted in statistically significant differences (p<0.05) in (Neutrophil ، Lymphocyte ، Monocyte ، and Eosinophil) levels compared to Group I rats negative control group ، Animals treated in Group V showed statistically significant reduction in (Monocyte and Eosinophil) levels (P<0.05) and non-significant reduction in (neutrophil and lymphocyte) compared to Group II. Group VI revealed a significant reduction in (neutrophil and monocyte ) and nonsignificant with (lymphocyte and eosinophil) (P<0.05) of rats compared to Group III ، furthermore group V showed significant reduction in neutrophil ، lymphocyte and elevation of monocyte and eosinophil compared with group VI ، these results consistent with previous studies (37) but inconsistent with some studies (38) authors mentioned all blood parameters decline except lymphocyte and eosinophil after levofloxacin treatment (25mg) ، in these study all blood parameters decline when dose of levofloxacin increased to (100mg/kg/day).the level of (platelets and W.B.C) showed nonsignificant difference (P>0.05) of rats that weretreated in Group II (reduction platelets and elevation WBC) compared with corresponding level in negative control Group I rats maybe due to inflammation . Similarly ، non -significant difference (P>0.05) was observed in (platelets and WBC) level in Group III compared to negative control Group I rats.…”
Section: Discussionsupporting
confidence: 90%
“…Panax Ginseng is used in herbal medicine in numerous countries of the world to treat many diseases, as ginseng roots contain active ingredients (ginsenosides), which have proven effective in improving immune functions, reducing mental strain and stabilizing blood pressure. Ginseng is also used as a physical performance enhancer 12 . Several studies managed on the pharmacological characteristics of ginseng extract indicated that its act to reduce fat, anti-allergy, anti-inflammatory, anti-diabetic, anti-stress, anti-depressive, anti-aging, antifatigue and anti-adhesion, as well as improving the functioning of the cognitive system and memory, preventing the growth of cancer cells as well as acting as an anti-inflammatory, Antioxidant, relieves menopausal symptoms, protects heart from diseases, protects against neurological disorders, and act to reduce high pressure 13,14,15 .A study showed that ginseng act to diminish fatty tissue and prevents fatness in diet-induced beefy mice 16 ginseng is used to treat liver degenerative diseases 17 ginseng root powder is beneficial for liver damage resulting from cholesterol-rich food, and these beneficial effects of ginseng as a result of containing The ginsenosides that reduce the level of liver enzymes 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The word Panax indicates that ginseng possesses medicinal properties for all diseases of the body 7 Its grows mainly in the cool regions in eastern Siberia, Korea and northern China , It has been used as a traditional medicine for thousands of years in East Asian countries to treated diseases, In past decades, ginseng has become one of most famous herbs in the world 8 , Its consists of 10% of inorganic materials and 80-90% of organic materials. Ginsenosides are the main active substances in ginseng 9 . It contains polysaccharides, peptidoglycans carbohydrates, amino acids, , some enzymes, fatty acids ,Vitamins, minerals, phytosterols , phenolic compounds and alkaloids 10 .…”
Section: Introductionmentioning
confidence: 99%